Industry 4.0 Driven Result-oriented PSS: An Assessment in the Energy Management - Sassanelli, Claudio; Arriga, Tiziano; Zanin, Stefano; D'Adamo, Idiano; Terzi, Sergio (International Journal of Energy Economics and Policy, 2022)
Sustainability is a current challenge and all sectors, including the buildings one, are being called upon to provide a solution to mitigate climate change. The state of the art of energy management using ICT technology in building systems industry is characterized by a traditional monitoring approach which could assess the energy consumption of the building but that cannot manage and act the required action to improve the energy management according to a demand side approach. The aim of this paper is to overcome this traditional monitoring approach, presenting Simon, a new model proposed by Evogy, enabling a result-oriented Product Service System (PSS) for buildings through Cyber-Physical Systems, Artificial Intelligence, and Internet of Things adoption. The main findings highlight the benefits associated with the Simon model by virtue of digital-based predictive maintenance on the real system. In addition, its adoption allows the PSS provider to aggregate energy demand from the plethora of buildings and, according to digital technologies, not only monitor consumption but also implement equipment. Finally, the application case highlights the benefits are different and thus stands as a best practice for combining sustainability and digitization.